Is MR imaging correlated with mid-term clinical results after arthroscopic all-inside meniscal repair? (Annals of Medical Research, 2021)
Aim: To research the correlation between clinical and radiological results after arthroscopic meniscus repair with all-inside suture technique and to assess the magnetic resonance imaging (MRI) diagnostic value on previously repaired meniscus.Materials and Methods: Fifty-two patients were included in the study.All-inside suture technique with a Fast-Fix suture device was used for all patients. After at least 24 months follow-up, the affected knee was checked with 1.5 Tesla MRI if there was an additional pathology or the meniscal pathology persisted with criteria of Crues et al. International Knee Documentation Committee (IKDC) and Lysholm scores were used for evaluation of the functional status of patients. Barrett’s criteria wascriteria were used for failure rates and clinical improvement. Correlation between clinical results and MRI findings were investigated.Results: The mean follow-up was 39.6 (range, 24–60) months. The mean age was 31.4 (range, 21–45) years. At the last time follow up the mean IKDC and Lysholm scores were improved significantly (p0.001). Healing in RR zone tears were significantly better than for the RW zone according to the clinical scores (p=0.02). MRI had one false negative and 11 false positive resultsresult when compared with the clinical results. In radiological results, repairs after at least 8 weeks were different from early repairs and had significantly higher failure rates (p=0.01).Conclusion: Clinical examination and radiological investigation for meniscal healing with 1.5 Tesla MRI gave significantly different healing and failure rates (p=0.006).Evaluating a previously repaired meniscus with MRI is controversial.
Keywords: Meniscus; correlation; clinical examination; all inside; magnetic resonance imaging; results.